Peran Mediasi Kepuasan Kerja pada Pengaruh Budaya Organisasi dan Komitmen Organisasi pada Kinerja Pegawai - Fernando Johanis Bolung (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This study aims to determine the influence of organizational culture and organizational commitment on employee performance with job satisfaction as an intervening variable at Bank Mandiri Manado. The results show that organizational culture has a positive and significant influence on employee performance, while organizational commitment does not have a significant influence on employee performance. Organizational culture does not have a significant influence on job satisfaction, but organizational commitment has a positive and significant influence on job satisfaction. Job satisfaction has a positive and significant influence on employee performance. Furthermore, job satisfaction does not mediate the relationship between organizational culture and employee performance, but job satisfaction mediates the relationship between organizational commitment and employee performance. The results of this study indicate that organizational culture and job satisfaction play an important role in improving employee performance at Bank Mandiri Manado, while organizational commitment plays an important role in increasing employee job satisfaction. Therefore, Bank Mandiri Manado needs to strengthen its organizational culture and increase employee job satisfaction to improve organizational performance.